THE IMPACT OF MARKETING STRATEGIES TOWARDS COMPANY PERFORMANCE AT PT. BINTANG HARAPAN UTAMA MEDAN - Edward Harnjo; Diana Afriani; Eddy, Eddy; Erina Alimin (Journal of Innovation Research and Knowledge, 2022)
Marketing strategy is needed for company to achieve the targeted goals of the company. Company usually will have goals in increasing the sales and maximizing the profit. Marketing strategy is very important for the company to expand the aims and goals of the company. A business cannot survive if its products or services not sold in the market. Thus, all marketing activities are undertaken to support the marketing strategy. The importance of marketing strategy is as important element as the increasing the company performance of the company. The purpose of this study is to know the impact of marketing strategy towads company performance in PT Bintang Harapan Utama Medan. Type of the research design used in the research is the descriptive method and correlational method. Population in this research is employees at PT Bintang Harapan Utama with 35 employees. The writer takes the sample which are 35 employees too. Data collection methods which used are descriptive statistic analysis, validity and realibility test, normality test, simple linear regression, coefficient correlation, coefficient of determination and Z test. The conclusion of this research is marketing strategy has impact towards company performance in PT Bintang Harapan Utama Medan. It can be proved by Z test that show Zcount (5.25) > Ztable (0.1). The high level of marketing strategy can lead the high level of company performance in PT Bintang Harapan Utama Medan. It can be seen of this relationship from coefficient correlation value which is 0.902 and coefficient determination value is 81.3%. From regression equation Y = 351 + 0.815 X, it can be seen that with increasing the marketing strategy in 1 unit, it will make increasing in company performance in 0.815 unit.